A study of the desirable and undesirable qualities of a school principal as judged by teachers - De la Paz, Felisa (Mallari) 1905- (University of the Philippines], 1953)
This study presents the most vital problems in administration and supervision, the desirable character of an administrator, and probable solutions to the problems that beset present conditions, and the teacher-administrator relationships, the pupil-principal relations, and the principal-community relations. The desirable and undesirable qualities and character traits of a school principal in connection with administration and supervision of an elementary school based on the present trend of education are also measured and appraised.